Fabrication of microfluidic channel using micro end milling and micro electrical discharge milling - Ali, Mohammad Yeakub (Universiti Malaya, 2009)
This paper discusses the fabrication of microfluidic channels using micro end milling and micro electrical discharge (ED) milling on metals and polymers. The width of the microchannels fabricated by micro end milling was 100-800 µm with 1-2 aspect ratio. The average surface roughness values were 100-200 nm and 80-120 nm on metals and polymers respectively. The end milling was found to form more burrs on metallic surface. Micro ED milling, on the other hand, was capable to produce high aspect ratio microchannels on metallic materials without forming any burrs. Using this micro ED milling process, microchannels of 120 µm width and 8-9 aspect ratio were machined with 40-50 nm average surface roughness. Micro swiss-roll combustor mold cavity was machined by using micro ED milling.